Crime, Anti-Social Behaviour and Schools
XIII, 260 p.
Keywords: The behaviour and safety of children and young people in and around schools is a topic of world-wide concern. From school shootings and deaths on school premises to the everyday behaviour of young people in school, this book explores what is happening in schools in Britain and links it with evidence from elsewhere in the world.